Development and Validation of an Evaporation Duct Model. Part I： Model Establishment and Sensitivity Experiments - 丁菊丽 费建芳 黄小刚 程小平 胡晓华 季亮 (Journal of Meteorological Research, 2015)
Based on the Coupled Ocean-Atmospheric Response Experiment （COARE） bulk algorithm and the Naval Postgraduate School （NPS） model, a universal evaporation duct （UED） model that can flexibly accommodate the latest improvements in component （such as stability function, velocity roughness, and scalar roughness） schemes for different stratification and wind conditions, is proposed in this paper. With the UED model, the sensitivity of the model-derived evaporation duct height （EDH） to stability function （ψ）, ocean wave effect under moderate to high wind speeds, and scalar roughness length parameterization, is investigated, and relative contributions of these factors are compared. The results show that the stability function is a key factor influencing the simulated EDH values. Under unstable conditions, the EDH values from stability functions of Fairall et al. （1996） and Hu and Zhang （1992） are generally higher than those from others; while under stable conditions, unreasonably high EDHs can be avoided by use of the stability functions of Hu and Zhang （1992） and Grachev et al. （2007）. Under moderate to high wind speeds, the increase in velocity roughness length z0 due to consideration of the true ocean wave effect acts to reduce modeled EDH values; this trend is more pronounced under stable conditions. Although the scalar roughness length parameterization has a minor effect on the model-derived EDH, a positive correlation is found between the scalar roughness length z0q and the model-derived EDH.